Motivational Dynamics of Educational Stress - Shukla, Ruchi (JOURNAL OF INDIAN EDUCATION, 2019)
One can understand educational stress by examining how the different need aspects of intrinsic motivation are interrelated and how they function to mediate the level of experienced stress by individual students. Analysis of the relationship between schooling experiences, parental expectations and the experience of educational stress can be understood in the Self-determination Theory (Ryan and Deci, 1985) framework in which sense of autonomy, self-efficacy or competence and relatedness can be said to affect the degree of internalisation of the motivation for school-related performance, which in turn would be related to experiencing of educational stress.